Impact of Regional Cerebral Perfusion on Outcomes Among Neonates Undergoing Norwood Operation. Issue 3 (May 2019) - Migally, Karl; Rettiganti, Mallikarjuna; Gossett, Jeffrey M.; Reemtsen, Brian; Gupta, Punkaj
Objectives: To evaluate the impact of regional cerebral perfusion (RCP) during heart operation on outcomes in neonates undergoing Norwood operation. Methods: We performed a retrospective cohort study using data from the Single Ventricle Reconstruction trial data set. The adjusted effect of RCP use on each outcome was studied using a penalized logistic regression model with bootstrap validation. Results: Of 549 patients included in the study, 252 patients (45.9%) received RCP during their heart operation. In univariate comparisons, the majority of the baseline characteristics and preoperative risk factors were similar in the RCP and No RCP group. The total cardiopulmonary bypass (CPB) time and the total cross-clamp (CC) time were longer in the RCP group (RCP vs No RCP, median CPB time: 161 minutes vs 109 minutes; median CC time: 63 minutes vs 43 minutes). In adjusted models, the use of RCP was not associated with decreased mortality and/or need for heart transplant at hospital discharge (odds ratio [OR]: 0.73; 95% confidence interval [CI]: 0.43-1.25) or prolonged mechanical ventilation (OR: 1.20, 95% CI: 0.62-2.28) or prolonged hospital length of stay (OR: 1.30, 95% CI: 0.73-2.30). We demonstrated that use of RCP was associated with longer CPB times, increased use of ultrafiltration, and higher probability of open chest after Norwood operation. Conclusions: This study did not demonstrate any impact of RCP on in-hospital mortality and/or heart transplantation, prolonged mechanical ventilation, and prolonged hospital length of stay among neonates undergoing Norwood operation.